Motivational Belief And Self-Regulated Learning A Study On Malaysian Students. - Melissa Ng, Lee Yen Abdullah; Abu Bakar, Kamariah (2006)
This study explored the relationships between self-regulated learning and selected motivational beliefs, namely self-efficacy, control beliefs, and anxiety of Malaysian students.